2020
DOI: 10.3920/wmj2019.2507
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of ochratoxin A and its stereoisomeric degradation product in various types of coffee available in the Czech market

Abstract: Ochratoxin A (OTA) belongs among the most frequently occurring mycotoxins in coffee. In order to investigate its contamination levels in products currently available in the market, a broad set of coffee samples (103 in total) collected between 2016 and 2018 in the Czech Republic was investigated. Aqueous-methanolic extracts purified by using immunoaffinity columns were analysed by ultra-performance liquid chromatography coupled with tandem mass spectrometry (U-HPLC-MS/MS). The undertaken study revealed a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Immunoaffinity columns filled with some mono/polyclonal antibodies reacting with some specific mycotoxins enable a very high level of sample purification regardless of the matrix complexity, that way improving the accuracy of the analytical method. Such columns were used by several authors of papers on OTA [ 22 , 23 , 24 ] and on 2′ R -OTA in coffee and cocoa [ 18 , 25 ]. We have also used some columns showing affinity to both OTA and 2′ R -OTA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoaffinity columns filled with some mono/polyclonal antibodies reacting with some specific mycotoxins enable a very high level of sample purification regardless of the matrix complexity, that way improving the accuracy of the analytical method. Such columns were used by several authors of papers on OTA [ 22 , 23 , 24 ] and on 2′ R -OTA in coffee and cocoa [ 18 , 25 ]. We have also used some columns showing affinity to both OTA and 2′ R -OTA.…”
Section: Resultsmentioning
confidence: 99%
“…These results agree with those reported by majority of other authors: range 0.17–6.29 µg/kg, i.e., below the EC accepted limit [ 22 , 32 , 36 , 37 ]. However, Jonatova et al [ 25 ] reported somewhat wider range from 0.2 to 12.8 µg/kg (average 2.9 µg/kg), what means that the most contaminated samples exceeded the limit. Somewhat higher contamination levels in instant coffee may be related to its last production stage: extract from the roasted coffee may contain more OTA than non-extracted coffee forms [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…This survey also reported that no significant difference was found between normal and decaffeinated instant coffee. Subsequently, 103 coffee samples were collected from Czech markets [65]. The results showed that 71% of roasted coffee samples were positive in the range of 0.2-2.5 µg/kg, and all the instant coffee samples were positive with concentrations between 0.6 and 12.8 µg/kg.…”
Section: Ota In Coffeementioning
confidence: 99%